Refocusing my family : coming out, being cast out, and discovering the true love of God - Cantorna, Amber (Theology for the people., 2017)
In 2012, at the age of twenty-seven, Amber Cantorna came out to her family as gay. As the daughter of a Focus on the Family executive, that transparency cost her everything. Refocusing My Family is Amber's journey from the suffocating expectations of Focus on the Family to the liberating joy of claiming her own identity. A powerful story of survival, Amber's struggle under the weight of perfectionism, reputation, and appearances is transformed into freedom when she boldly steps into her identity and discovers that the true love of God surpasses all.